Linguistic construction of justice: a pragmatic analysis of judges’ reasoning in Indonesian constitutional court decisions - Sadani (Indonesian Journal of Linguistics and Legal Discourse, 2026)
Background: Judicial decisions of constitutional courts not only resolve disputes but also construct justice through language, making the study of linguistic strategies in legal reasoning crucial in politically sensitive contexts. Objective: The purpose of this research is to examine how Indonesian Constitutional Court judges employ pragmatic strategies, argumentative structures, and modality to construct authority and legitimacy in their reasoning. Method: Using a qualitative, descriptive design, the study analyzed a corpus of five landmark Constitutional Court decisions, complemented by hearing transcripts and press releases, through pragmatic, argumentative discourse, and modality analysis. Results: The findings reveal three main patterns: first, judges frequently use implicatures, presuppositions, and indirect directives to embed implicit meanings and soften confrontational reasoning; second, deductive, analogical, and enthymematic structures are strategically combined to balance constitutional certainty with rhetorical persuasion; third, modality—especially deontic expressions like must and shall—dominates, alongside epistemic hedging and evaluative judgments, reflecting the Court’s dual need for authority and flexibility. Implication: These findings imply that judicial authority is linguistically constructed, and that pragmatic, argumentative, and modal strategies function not only to justify decisions but also to sustain public trust and democratic legitimacy. Novelty: This study demonstrates how pragmatic, argumentative, and modal strategies are strategically orchestrated in constitutional court decisions to construct judicial authority while negotiating legitimacy in politically sensitive contexts.